State Defense Perspective: Disaster Risk Analysis of Air Transportation Accidents - Pamungkas, Bagus Ajar; Aritonang, Sovian (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2017)
The aim of this study was to analyse disaster risk of air transportation accidents in the national defense system perspectives and also the efforts of airport authority to manage the risk. A qualitative, narative and exploratory study was developed using risk management ISO 31000 as a method to analyse data. Interview, literature study and documentation were done to collect data. This study used purposive sampling to decide informants. It was found that Halim Perdanakusuma International Airport had a high risk in air transportation accidents. To keep the stability of national defense, the risk had to be managed through structural mitigation and non-structural mitigation